Phenolics Profile of a Naturally Debittering Olive in Comparison To Regular Olive Varieties - Aktaş, Ayşe Burcu; Özen, Banu; Tokatlı, Figen; Tokatlı, Figen; Şen, İlknur; Şen, İlknur; Özen, Fatma Banu (John Wiley and Sons Inc., 2014)
BACKGROUND: Hurma, an olive variety that grows in a specific area in Turkey, loses its bitterness before harvesting, and therefore does not need further processing steps for the production of table olives. The total phenol content and phenolic profiles of (1) this naturally debittered olive type, Hurma; (2) the same olive variety, but not a naturally debittered type, Erkence; and (3) another variety, Gemlik, which is commonly consumed as table olive, were determined during their maturation period for two harvest years. RESULTS: The total phenol content of Hurma is the lowest compared to the other types regardless of harvest year, which has a significant effect on the phenolic content and composition of individual components for all olive types. All three olive types can be differentiated from each other especially during the late phase of maturation using the phenolics profile in combination with principal component analysis. CONCLUSION: The natural debittering phenomenon of Hurma olive on the tree involves a decrease in phenol content and a change in phenol composition. The differentiation in phenol composition especially becomes very significant in the late of period of maturation.
Keywords: Debittering; Maturation; Olive; Phenolics